Konsep Moderasi Pidana Mati RKUHP dalam Perspektif HAM dan Kepentingan Negara - Triantono Triantono; Muhammad Marizal (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
The debate over the imposition of the death penalty has long existed between the Abolitionists and Retentionists. The core problem of the debate is that the death penalty intersects with human rights and the interests of the state in maintaining public order. Indonesia, which chooses to apply the death penalty, cannot be separated from these two problematic aspects. This study aims to answer two problems: first, the death penalty debate in Indonesia including its historical aspects; second, the concept of middle ways (moderation) of the death penalty in the Draft of the Criminal Code (RKUHP). This is a normative legal research in which data are collected through library research on legal materials. The gathered data are analyzed in a qualitative description to answer the problems posed in the research. The results of the study show that the death penalty has become a part of the history of Indonesia due to the complexity of the legal system in Indonesia which is influenced by the Dutch, local custom, and Islamic legal systems. The concept of a middle way (moderation) of the death penalty in the RKUHP has placed the death penalty not as a principal penalty but is specific and alternative. Its implementation is also carried out after the probationary period. This is an interesting concept to bridge the death penalty debate in Indonesia. However, there are still problems related to changes to the death penalty, clemency issues, the length of delay in the death penalty and institutions that can amend the death penalty. In addition, there are also problems in determining the death penalty as a result of very serious crimes, because the indicators of most serious crimes have not been determined in a harmonious and consistent manner.